Rasio Keuangan Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2024 - Tri Nurdyastuti; Suroto Suroto; Juan Anthony (Excellent, 2025)
This study aims to analyze the effect of financial ratios consisting of profitability, liquidity, and solvency on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. The study employs a quantitative approach using multiple linear regression analysis. Hypothesis testing is conducted using the t-test to measure the partial effect of each variable, the F-test to examine the simultaneous effect, and the coefficient of determination (R²) to determine the extent to which the independent variables contribute to the dependent variable. The results show that the profitability variable (X1) has a positive and significant effect on financial performance. Conversely, the liquidity variable (X2) has a negative and insignificant effect on financial performance. The solvency variable (X3) also has a negative and insignificant effect on financial performance. The coefficient of determination (R²) of 0.749 indicates that profitability, liquidity, and solvency collectively explain 74.9% of the variation in financial performance, while the remaining 25.1% is influenced by other variables outside the scope of this model. These findings imply that profitability is the primary indicator influencing the financial performance of banks; therefore, management should prioritize strategies that enhance efficiency and competitiveness.